2017
DOI: 10.1177/1076029617733040
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of CYP 4501A2 Activity by Total Overnight Salivary Caffeine Assessment (TOSCA) in Patients on Warfarin Treatment: A Cross-Sectional Study

Abstract: Warfarin is an oral anticoagulant, commonly used for primary and secondary prevention of venous and arterial thromboembolic events. The drug is characterized by narrow therapeutic index, widespread individual variability in clinical response, and high rates of adverse events, particularly bleeding complications. For these reasons, a close monitoring of the dosage, using the frequent assessment of coagulation status by means of International Normalized Ratio value, is mandatory. Warfarin is metabolized by hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The variants of cytochrome P450 and paraoxonase can lead to the change of enzyme activity, especially the mutation of CYP2C19*2, CYP2C19*3, PONQ192R allelic [17,18]. The probe drug could be used to measure the activity of CYP450 and to point out the genotyping of CYP450 [19]. Ersin Gumus etal evaluate lansopranzole as an in vivo phenotyping probe for assessing CYP2C19 activity, they found that the poor metabolizers have lower enzyme activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…The variants of cytochrome P450 and paraoxonase can lead to the change of enzyme activity, especially the mutation of CYP2C19*2, CYP2C19*3, PONQ192R allelic [17,18]. The probe drug could be used to measure the activity of CYP450 and to point out the genotyping of CYP450 [19]. Ersin Gumus etal evaluate lansopranzole as an in vivo phenotyping probe for assessing CYP2C19 activity, they found that the poor metabolizers have lower enzyme activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…For TDM, unstimulated saliva samples were collected by expectorating or with the help of a saliva collection device such as Salivette ® (Sarstedt, Nümbrecht, Germany). In some cases, saliva excretion is stimulated by paraffin wax ( Cohen et al, 1985 ; Tarantino et al, 2018 ) or citric acid ( Kirk et al, 1994 ; Kopecky et al, 1997 ) and collected by similar methods. For younger children, saliva collection is usually performed with the help of an adult and a variety of devices and collection methods to facilitate sample collection.…”
Section: Point-of-care Collection Of Saliva or Sweat For Precision Do...mentioning
confidence: 99%